Benefits of Football Competition in the Economy of Traders in Surajaya Stadion Lamongan - Anas, Fahmi (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
Football is one of the most popular sports insociety. People could enjoy football games throughtelevision or see it directly at the stadium. Football has ahuge impact on the economy. Football benefit society,especially a group of traders who are in Indonesia.Merchants can take advantage and benefit of thepresence of football competition in the field of economy.The methods used in this study is descriptive qualitative.The informants in this study are Surajaya Stadiumtraders. The process of collecting data throughobservation, interviews and the literature review.Techniques in analyzing data using interactive datacollection and presentation of data. The theory used toanalyze is of George Homans Exchange theory. Thefindings from the data in this study there are severalvariations of data about football and economy, throughsuccess and stimulus proposition. The findings from theinterviews, it was discovered that, football in the stadiumSurajaya was able to increase revenue for the Group ofmerchants, ranging from food, beverages, accessoriesand jersey. Traders choose Open lapak selling aroundthe stadium felt getting a lot of profit. Traders choose toopen stalls selling around the stadium because of theenthusiasm of the people who come to see footballmatches at the Stadium Surajaya.